Activated Carbon from Biomass Transfer for High‐Energy Density Lithium‐Ion Supercapacitors. Issue 18 (4th July 2016) - Li, Bing; Dai, Fang; Xiao, Qiangfeng; Yang, Li; Shen, Jingmei; Zhang, Cunman; Cai, Mei
Abstract : High‐performance activated carbons derived from the most common egg white are synthesized via a simple biomass transfer process. Hybrid‐type lithium‐ion supercapacitors (LICs) are fabricated utilizing the eAC as the cathode materials and Si/C nanocomposites as the anode material. The LIC exhibits high energy density and power density with an excellent cycling life.